한국 노인의 수산물 섭취 추이 및 이에 영향을 주는 요인에 관한 연구 －2009~2019 국민건강영양조사를 이용하여 - 장원(Won Jang); 조정희(Jung-Hee Cho); 이동림(Donglim Lee); 김양하(Yangha Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
본 연구에서는 국민건강영양조사 자료를 기반으로 2009년부터 2019년까지 10년간 우리나라 노인의 평균 수산물 섭취량과 수산 단백질 섭취 비율의 연차적 추이를 분석하였다. 또 수산물 섭취와 사회경제적 요인과의 관련성을 분석하였으며 결과는 다음과 같이 요약된다. 지난 10년간 우리나라 노인의 평균 수산물 섭취량은 전반적으로 증가하는 추이를 보였으나(P-trend<0.0001), 멸치육수, 다시마 육수 등 액체 섭취량을 제외한 수산물 섭취량은 통계적으로 유의적인 경향성을 보이지 않았다(P-trend=0.8867). 2019년 기준으로 전체 국민의 경우 동물성 단백질 급원으로 육류로부터 공급되는 단백질의 비율이 어패류로부터 공급되는 단백질보다 약 2배 높았다. 본 연구에서 노인의 경우 동물성 단백질 급원으로 육류와 어패류의 기여 비율이 각각 14.4%, 11.7%로 거의 비슷하여 노인에게 어패류가 매우 중요한 동물성 단백질 공급원임을 알 수 있었다. 노인의 수산물 섭취에 영향을 미치는 사회경제적 요인으로 교육수준이 높을수록(P<0.0001), 경제수준이 높을수록(P<0.0001) 수산물 섭취 수준이 높았다. 본 연구 결과는 수산물 섭취에 취약한 노인집단을 선별하여 수산물 섭취와 관련 있는 사회경제적 요인의 영향을 최소화하여 노인들의 수산물 섭취 증가를 통한 영양학적 편익을 도모하기 위한 과학적 근거를 제공한다는 점에서 중요한 의미가 있다. The present study aimed to delineate yearly trends in the daily consumption of seafood and investigate the socioeconomic factors influencing seafood consumption among elderly Koreans. Data from the 2009 to 2019 Korea National Health and Nutrition Examination Survey (KNHANES) was used, and a total of 12,171 subjects aged 65 years or older were included in this study. Seafood intake was assessed by a 24-hour dietary recall. Yearly trends of seafood or protein intake were analyzed via multiple regression analysis. The results showed that the consumption of seafood, including fish, shellfish, and seaweed increased during the past decade (P<0.0001). However, there was no statistically significant difference in seafood consumption trend when fish stock intake was excluded. In 2019, the population’s animal protein intake through meat was approximately twice that through seafood. However, for elderly subjects in the study, meat accounted for 14.4% and seafood 11.7% of the animal protein intake showing that seafood is a crucial source of animal protein. There was a significant correlation between seafood intake and educational level (P<0.0001) and family income (P<0.0001). Socioeconomic factors such as higher levels of education and income correlated with greater consumption of seafood. This study provides significant scientific evidence to show that there are disadvantaged groups who have difficulty accessing and consuming sufficient seafood, and points to the need to decrease socioeconomic barriers to promote increased seafood intake in the elderly population. KCI Citation Count: 1